Universal design of urban spaces in Ukraine: problems and prospects - Novoselchuk, Natalia; Shevhenko, Liudmyla; Troshkina, Olena; Troshkin, Arsenii (Landscape Architecture and Art, 2025)
The issue of the development of the concept of universal design in Ukraine at the present stage is considered in the article. The general state of the solution of this issue is characterized and statistical data is provided. Using the example of Ukrainian cities, in particular the city of Poltava, the main problems and prospects for development that require gradual resolution are outlined. The main task is to ensure the accessibility of the urban environment by creating comfortable conditions for using the housing and communal infrastructure and equipping buildings, taking into account the needs of low-mobility population groups. The object of the study is urban spaces and streets from the point of view of their barrier-free nature and landscape organization. To achieve the set goal, various scientific methods were used in the work. In particular, the empirical method was used for the purpose of observation and comparison. The theoretical method was used to process historical data on the development of the spaces and streets selected for the study. The method of field surveys helped to identify existing problems in the studied areas of the city. And the method of experimental design contributed to the implementation of the main techniques and recommendations in practice. The result of the research is the analysis and development of a number of project proposals taking into account the principles of universal design and modern landscape organization. Currently, for Ukraine, solving the problems of disability and low-mobility population groups is one of the priority areas of the state’s social policy. A significant impetus is the ongoing russian-Ukrainian war. Since the number of people with disabilities who received it as a result of the war is growing every day. True accessibility and barrier-freeness covers all spheres of public life. Universal design is not limited to accepted principles, laws or prescribed rules. It includes respect for other people’s borders, a human-centric approach, concern for comfort for everyone and the understanding that human needs are noticed. We can talk about full inclusion only when every person has unhindered access to buildings, education, the Internet, has the opportunity to work and freely use transport. Ukraine, which is becoming a veteran-centric state in the realities of war, is obliged to be inclusive.